A Review of Explicit and Implicit Assumptions When Providing Personalized Feedback Based on Self-Report EMA Data - Leertouwer, IJsbrand; Cramer, Angélique O. J.; Vermunt, Jeroen K.; Schuurman, Noémi K. (Frontiers in Psychology, 2021)
Ecological Momentary Assessment (EMA), in which participants report on their moment-to-moment experiences in their natural environment, is a hot topic. An emerging field in clinical psychology based on either EMA, or what we term Ecological Retrospective Assessment (ERA) as it requires retrospectivity, is the field of personalized feedback. In this field, EMA/ERA-data-driven summaries are presented to participants with the goal of promoting their insight in their experiences. Underlying this procedure are some fundamental assumptions about (i) the relation between true moment-to-moment experiences and retrospective evaluations of those experiences, (ii) the translation of these experiences and evaluations to different types of data (iii) the comparison of these different types of data (iv) the impact of a summary of moment-to-moment experiences on retrospective evaluations of those experiences. We argue that these assumptions deserve further exploration, in order to create a strong evidence-based foundation for the personalized feedback procedure.